2017
DOI: 10.1080/08946566.2017.1365031
|View full text |Cite
|
Sign up to set email alerts
|

The National Elder Mistreatment Study: An 8-year longitudinal study of outcomes

Abstract: Outcomes of elder mistreatment have not been studied prospectively in a national sample. The NEMS 8-year follow-up findings indicate a strong relationship between elder mistreatment at Wave I and negative emotional and physical health 8 years later. Fortunately, current (Wave II) social support appears to be both consistently and powerfully protective against most negative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 30 publications
2
38
0
6
Order By: Relevance
“…It has also been mentioned that the record and measurement forms are insufficient and underdeveloped in the region 30 . In fact, Acierno et al ., found that approximately 11% of elderly adults experience abuse each year, but only 1 out of 14 cases is reported to authorities; and it is suggested that for every documented abuse case, 24 cases are not reported 27 , 31 . According to the First inter-sectorial report, violence against the elderly people , of the Mayor Office of Bogotá 32 , some situations of abuse are evident, especially in cases related to physical aspects and neglect of the elderly person, which makes it easier for identification and intervention by society and the State; but other types of violence, such as sexual, psychic, emotional or economic abuse are more difficult to detect and are not reported, either because the elderly people have got used to this type of relationship, because of being afraid of losing their network support, or because of naturalization of this situation within families 32 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been mentioned that the record and measurement forms are insufficient and underdeveloped in the region 30 . In fact, Acierno et al ., found that approximately 11% of elderly adults experience abuse each year, but only 1 out of 14 cases is reported to authorities; and it is suggested that for every documented abuse case, 24 cases are not reported 27 , 31 . According to the First inter-sectorial report, violence against the elderly people , of the Mayor Office of Bogotá 32 , some situations of abuse are evident, especially in cases related to physical aspects and neglect of the elderly person, which makes it easier for identification and intervention by society and the State; but other types of violence, such as sexual, psychic, emotional or economic abuse are more difficult to detect and are not reported, either because the elderly people have got used to this type of relationship, because of being afraid of losing their network support, or because of naturalization of this situation within families 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The consistent failure to report emotional mistreatment across both perpetrator types, in the context of a willingness to report financial mistreatment when perpetrated by a stranger, suggests that victims of this form of mistreatment may not be aware that it is a type of abusive, largely verbal behavior. This may speak to a general normative acceptance of psychological violence against older adults, and implies that education is needed across agencies and the general population regarding emotional abuse, its negative effects (Acierno, Hernandez-Tejada, Anetzberger, Loew, & Muzzy, 2017), and methods of reporting to police and other authorities.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare settings, such as primary care clinics or emergency departments, have been targeted as critical points of EA detection (Beach, Carpenter, Rosen, Sharps, & Gelles, 2016;Platts-Mills et al, 2018). A disproportionate number of EA victims interface with the healthcare system (Dong, 2015) and such visits may represent the only opportunity for detection among EA victims who are often socially isolated (Acierno, Hernandez-Tejada, Anetzberger, Loew, & Muzzy, 2017). EA victims may also present to healthcare settings due to injury or chronic illness precipitated by abuse/neglect.…”
Section: Introductionmentioning
confidence: 99%